A novel tool to assess the quality of RWE to guide the management of retinal disease. Issue 6 (28th December 2020) - Finger, Robert P.; Daien, Vincent; Talks, James S.; Mitchell, Paul; Wong, Tien Y.; Sakamoto, Taiji; Eldem, Bora M.; Lövestam‐Adrian, Monica; Korobelnik, Jean‐François
Abstract: Despite the growing importance of real‐world evidence (RWE) for guiding clinical decisions in retinal disease, there is currently no widely used guidance available for assessing the quality and relevance of RWE studies in ophthalmology. This paper summarizes the development of a user‐friendly tool that facilitates assessment of the quality of available RWE for neovascular age‐related macular degeneration (nAMD), diabetic macular oedema (DME) and retinal vein occlusion (RVO). A literature search was conducted to identify tools developed to assess the quality of RWE, in order to identify the most appropriate framework on which to base this tool. The Good Research for Comparative Effectiveness (GRACE) guidelines was chosen for this purpose as it is designed to assess the quality of observational studies and has been extensively validated, including demonstration of strong sensitivity and specificity. The GRACE guidelines were adapted to develop a straightforward tabular tool that allows simple assessment and comparison of the quality of published evidence in retinal disease for researchers and physicians alike, and includes guidance on treatment details, outcome measures, study population, and controlling for bias. The newly developed tool provides a simple method to support assessment of the strength of evidence and certainty of conclusions drawn from RWE in retinal disease, to ensure clinical decision‐making is influenced by the highest quality evidence.